Gambaran Perilaku Penggunaan Suplemen Herbal dan Non Herbal selama Pandemi Covid-19 - Dwiyanti, Septika; Dewi, Wan Nishfa; Woferst, Rismadefi (Jurnal Vokasi Keperawatan (JVK), 2023)
During the Covid-19 pandemic in Indonesia, the use of herbal and non-herbal supplements in preventive and curative efforts increased significantly. Using supplements prevents Covid-19 from complementing vitamin deficiencies in certain conditions. This study aims to identify the behavior of herbal and non-herbal supplements during the Covid-19 pandemic.  This study is retrospective. The number of samples used in this study was 99 respondents were selected using the quota sampling technique. Data was collected using a questionnaire to identify behavioral variables, and validity and reliability tests of this questionnaire were carried out. Data were analyzed using descriptive analysis.  The results of this study indicate that the majority of respondents' age is in the range of 17-25 years (54.4%), most of the respondents were female 64 people (64.6%), the behavior of using herbal and non-herbal supplements seen from the indicator of being aware of side effects is 74.7%, from the indicator the way to store supplements is 58.6%, from the indicator the way to dispose of expired supplements is 48.5% and from indicator types of herbal supplements 71.7%. The results of this study provide implications for the community to apply appropriate behavior in using health supplements.